SEM and TEM evidence of mixed-layer illite-smectite formed by dissolutioncrystallization processes in continental Paleogene sequences in northwestern Argentina. (1st December 2016) - Do Campo, Margarita; Bauluz, Blanca; Nieto, Fernando; Del Papa, Cecilia; Hongn, Fernando
In the northernmost Calchaquí Valley (Salta, Argentina), the Paleogene continental sediments show a transition from smectite, at the top, to R3 I-S (>90% illite) through R1 I-S (65–80% illite), in contrast to the remaining sectors, containing smectite up to the bottom. Samples at the base of the succession were characterized by high-quality step-scan X-ray diffraction (XRD), scanning electron microscopy (SEM) and analytical high-resolution transmission electron microscopy (HRTEM). Analysis by SEM demonstrated dissolution of primary phases (feldspars, micas and quartz) and crystallization of illite, I-S and kaolinite. As this alteration is not pervasive, an intermediate fluid/rock ratio could be inferred. The lattice-fringe images of the samples from upper parts of the sequence show abundant I1-rich areas, whereas in the lower parts of the sequence, illite packets and I3 I-S coexist and compositions evolve towards muscovite (tetrahedral-charge increase, principally compensated by Mgby-Al substitution in octahedral sites and by a slight decrease in Ca in interlayer sites). As burial temperatures were probably similar in all the samples, depth was not responsible for the illite formation at the bottom. The TEM textures suggest that illitization proceeded mainly by dissolution-crystallization. The active faults close to the northern Calchaquí Valley probably promoted the circulation of hot, deep fluids, favouring illitization.